Inactivated COVID-19 Vaccine Induces a Low Humoral Immune Response in a Subset of Dermatological Patients Receiving Immunosuppressants - Seree-aphinan, Chutima; Chanprapaph, Kumutnart; Rattanakaemakorn, Ploysyne; Setthaudom, Chavachol; Suangtamai, Thanitta; Pomsoong, Cherrin; Ratanapokasatit, Yanisa; Suchonwanit, Poonkiat (Frontiers in Medicine, 2021)
Inactivated Sinovac-CoronaVac vaccine (Sinovac Life Sciences, Beijing) for coronavirus disease 2019 (COVID-19) has been used in many countries. However, its immunogenicity profile in immunosuppressed dermatological patients is lacking. This prospective observational case-control study compared the humoral immune response between adult dermatological patients receiving systemic immunosuppressive therapies (n=14) and those who did not (n=18); excluding patients with HIV infection, cancer, non-dermatological autoimmune conditions, previous COVID-19 infection, and positive anti-severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) IgG prior to vaccination. The subjects were advised to withhold methotrexate for one week after each vaccine dose while continuing other therapies unadjusted. Anti-SARS-CoV-2 IgG antibody, surrogate neutralizing antibody (sNAb), and seroconversion rates (calculated from the percentages of participants in the group with positive sNAb) were used to assess immunogenicity. We found that participants using azathioprine, ciclosporin, mycophenolate mofetil, or prednisolone > 10 mg/day had a lower level of serum anti-SARS-CoV-2 IgG antibody and sNAb than those received methotrexate < 10 mg/week, prednisolone < 10 mg/day, or biologics (i.e., secukinumab, ixekizumab, omalizumab). Patients who received methotrexate < 10 mg/week, prednisolone < 10 mg/day or the biologics had a similar immunogenicity profile to those without immunosuppressive therapies. Despite the lack of statistical significance, a reduction of humoral immune response was observed among the study participants who used > 2 immunosuppressants or pemphigus patients. Our findings suggest that a subset of patients with immune-mediated skin conditions respond poorly to the vaccine despite having low-level immunosuppression. These patients could benefit from vaccines that trigger a greater level of immunogenicity or booster doses.